The safety and anti-tumor effect of multiple peptides-pulsed dendritic cells combined with induced specific cytotoxic T lymphocytes for patients with solid tumors - Zhao, Xuan; Zhang, Zhen; Wen, Chunli; Huang, Jianmin; Yang, Shuangning; Liu, Jinyan; Geng, Huizhen; Peng, Bing; Li, Zibo; Zhang, Yi (Frontiers in Immunology, 2023)
Objective The aim of this study was to explore the safety and efficacy of multiple peptide-pulsed autologous dendritic cells (DCs) combined with cytotoxic T lymphocytes (CTLs) in patients with cancer. Methods Five patients diagnosed with cancer between November 2020 and June 2021 were enrolled and received DC-CTLs therapy. Peripheral blood was collected and antigenic peptides were analyzed. The phenotype and function of DC-CTLs and the immune status of patients were detected using flow cytometry or IFN-γ ELISPOT analysis. Results DCs acquired a mature phenotype and expressed high levels of CD80, CD86, CD83, and HLA-DR after co-culture with peptides, and the DC-CTLs also exhibited high levels of IFN-γ. Peripheral blood mononuclear cells from post-treatment patients showed a stronger immune response to peptides than those prior to treatment. Importantly, four of five patients maintained a favorable immune status, of which one patient’s disease-free survival lasted up to 28.2 months. No severe treatment-related adverse events were observed. Conclusion Our results show that multiple peptide-pulsed DCs combined with CTLs therapy has manageable safety and promising efficacy for cancer patients, which might provide a precise immunotherapeutic strategy for cancer.